Investigation of friction stir welding of aluminium alloy and aluminium matrix composites - Al-jumaili, Omar Saad salih (2018)
Friction stir welding (FSW) is an upgraded version of the conventional friction welding process, and it is considered the latest development and the most important one during the past two decades in the welding of metals. The dependence of FSW on friction and plastic work as a heat source precludes the melting in the workpiece and leads to avoiding many of the difficulties arising from the change in the state of the material, such as defects, distortion and residual stresses, which often happen in conventional welding processes. FSW gained significant attention as a solid-state welding process of aluminium alloys, but now there is a need to extend its application to advanced materials such as metal matrix composites (MMCs). However, the process has always represented a challenge owing to the complexity of microstructural development and the associated number of process parameters to take into consideration. This thesis investigates the feasibility of welding two new advanced aluminium matrix composites (AMCs), AA 6092/SiC/17.5p-T6 and AA 6061B/SiC/20p-T1 by FSW for the first time. Also, aluminium alloy AA6082-T6 has been investigated as base-line material to specify the benefit, drawback, and FSW window. Experiment analyses were conducted to evaluate the influence of FSW parameters, including tool rotation and traverse speeds on the quality of weldments. Weld joints were characterised in terms of thermal history, metallurgical behaviour, mechanical properties, and residual stresses. The metallurgical characterisations have been done by optical, scanning electron microscopy (SEM), electron backscattered diffraction (EBSD), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS). Microhardness, tensile, and low-cycle fatigue (LCF) test with the axial total strain-amplitude control mode R=ε_min⁄(ε_max=-1) were used for evaluating the mechanical properties. The results showed that the generated peak temperature in the welding joints is affected more significantly by the rotating tool speed, while the exposure time and subsequent cooling rate are controlled by tool traverse speed. The microstructure of nugget zone (NZ) exhibits an elliptical shape with a substantial grain refinement resulted from continuous dynamic recrystallisation (CDR) process with an increase in the fraction of high angle grain boundaries (HAGBs). The evolved grain size was greatly influenced by weld pitch as the ratio between tool traverse speed to tool rotation speed, which is a key parameter to control the amount of heat input, exposure time and cooling rate. In addition, in the case of AMCs more homogeneous distribution of reinforcement particles (SiC) coupled with particle refinement were formed in the NZ. The cross-weld microhardness proﬁle revealed a signiﬁcant difference in microhardness among the base metals, heat affected zone (HAZ), thermo-mechanically affected zone (TMAZ), and NZ in the case of AA 6082 and AMC (AA 6092/SiC/17.5p), as they depend on the strengthening precipitate. Meanwhile, the hardness profile of AMC (AA 6061B/SiC/20p) FSW joints showed that there is no difference in the measured hardness between the welding zone and base materials because the welded joints are exposed to thermal history similar to the initial heat treatment condition of the base metal, T1, cooled from an elevated temperature shaping process and naturally aged. The tensile strength of AA6082, and AMC (AA 6092/SiC/17.5p) cross-weld FSW specimens was found to be lower than their base metals with a joint efficiency (the ratio of the tensile strength of joint to the tensile strength of base metal) of about 71 and 75 %, respectively. While for SAMC (AA 6061B/SiC/20p) FSW joints it is reached 108 % of that of the base metal. The low-cycle fatigue results indicate that the fatigue life of the cross-weld joints varies with grain size in the NZ, and it is always lower than that of the base metal. A significant improvement in fatigue life is found to be related to the finer equiaxed grains dominated by HAGBs in the NZ, as well as, to less gradient in the grain size of the cross-weld. Residual stresses are significant concerns associated with the welding process, as it can combine with applied stresses, which may lead to the reduction of structural properties. The result of residual stress measurement by neutron diffraction techniques exhibited a typical ‘‘M’’ profile, which indicates that compressive and tensile residual stress existed in the base metal and welding zone, respectively. This has not only provided an improved understanding of residual stresses in FSW joints but also has contributed to the validation of 3D fully coupled thermo-mechanical finite element (FE) model, which has been developed based on Coupled Eulerian-Lagrangian (CEL) technique. The model is also used to predict the thermal history and material flow in the FSW of aluminium alloy AA6082. The numerical results showed a good agreement with the experimental results.